2004
DOI: 10.1111/j.1600-079x.2004.00153.x
|View full text |Cite
|
Sign up to set email alerts
|

The circadian rhythm of melatonin modulates the severity of caerulein‐induced pancreatitis in the rat

Abstract: Melatonin, an antioxidant, protects the pancreas against acute inflammation but, although this indole is released mainly at night, no study has been undertaken to determine circadian changes of plasma melatonin levels and the severity of acute pancreatitis. The aims of this study were: (a) to compare the severity of caerulein-induced pancreatitis (CIP) produced in the rat during the day and at the night, and (b) to assess the changes of plasma melatonin level and the activity of an antioxidative enzyme; supero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
33
0
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 47 publications
4
33
0
3
Order By: Relevance
“…No statistically significant difference was observed between group 1 and group 3 in terms of amylase levels. Despite one study reporting that melatonin has no effect on serum amylase levels [42], our results support the other reports that showed a decline in serum amylase levels following melatonin treatment [31,43,44].…”
Section: Discussionsupporting
confidence: 74%
“…No statistically significant difference was observed between group 1 and group 3 in terms of amylase levels. Despite one study reporting that melatonin has no effect on serum amylase levels [42], our results support the other reports that showed a decline in serum amylase levels following melatonin treatment [31,43,44].…”
Section: Discussionsupporting
confidence: 74%
“…Yapılan çalışmalar-da genellikle yaşlanma ile birlikte dokulardaki serbest radikal düzeylerinin arttığı bildirilmektedir [5][6][7]. Hem ekzokrin, hem de endokrin salgı yapan bir bez olan pankreasla ilgili yapılan çalışmalarda, yaş ilerledikçe serbest radikal düzeyinin arttığı, antioksidan kapasitenin ise düştüğü bildirilmiştir [8].…”
Section: Introductionunclassified
“…Melatonin decreased the edema in the pancreas and stomach, and also the extent of lipid peroxidation in the pancreas. Jaworek et al [30] . demonstrated that even the circadian changes in physiological levels of melatonin reduce the severity of experimental pancreatitis [30] .…”
Section: Introductionmentioning
confidence: 99%
“…Jaworek et al [30] . demonstrated that even the circadian changes in physiological levels of melatonin reduce the severity of experimental pancreatitis [30] . L-Arg-induced pancreatitis is an experimental model of severe necrotizing acute pancreatitis.…”
Section: Introductionmentioning
confidence: 99%